[Petition supporting HB 1617, employment discrimination ban] - BK; BROWN L; BROWN M; CJ; CLINTON S; DILGER RL; FOUST RC; SEATTLE FIRE FIGHTERS UNION; ILLEGIBLES; ILLEGIBLE # AFL CIO; JAEGER JA; JUDD R; LAMLAN L; LATHAM R; LAULAINEN E; MARSH G; WACHUCK RC; WESTBEY JP; WHITNEY EJ (Tufts Archival Research Center, 2007)
Handwritten; Petition letter supporting HB 1617, which bans employment discrimination based on off-duty tobacco use. States that it is a privacy issue, and should not be construed as support of tobacco use. Includes signatures and union affiliations of 23 supporters.